Chapter 5 An analysis of pertinent issues in education in Southern Europe - Mayo, Peter; Brown, Maria; Briguglio, Michael (Taylor & Francis, 2024)
This volume is the first of its kind to discuss social welfare issues using case studies from a broad range of Southern European countries, both large and small, a decade after the financial crisis. It identifies similarities and differences in the ways in which Southern European countries engage with specific welfare issues and examines whether Southern European welfare is distinct from that of the rest of the continent. The book also engages with the impact of COVID-19 on the social welfare issues under investigation. The volume is divided into four sections, each examining in detail issues including employment, education, health, sexuality, globalization, social movements and migration. With its contributions from experts in the field, the volume is recommended for academics, researchers and students of sociology, social policy, economics, education, politics and social movements.